Trauma radiology in northern Norway - Bågenholm, Anna (UiT The Arctic University of Norway, 2020)
Background: This thesis focuses on diagnostic imaging in potentially severely injured patients admitted to the University Hospital of North Norway. Imaging is important for timely initiation of treatment and survival after trauma. The use of standardized whole body computer tomography (SWBCT) is increasing. However, the ionizing radiation used may cause a small risk for induction of cancer later in life. The aim of this audit was to characterize the patients, validate the injury coding in the National trauma registry, and describe the diagnostic imaging used and doses delivered, to evaluate the degree of adherence to the International commission of radiological protection’s (ICRP) justification principles for dose optimization. Methods: We audited all 144 patients admitted with trauma team activation in 2015. Injury codes in the registry were validated against a consensus reference standard. All diagnostic imaging was registered. Dose area product (DAP) (X-ray), dose length product (DLP) (CT) and effective doses are reported. Patients were categorized into trauma admission CT examination strategy groups SWBCT, selective CT or no CT, and factors associated with examination strategy decisions analyzed. Results and conclusions: The patients were predominantly young men exposed to vehicle accidents. Few were severely injured and pre-hospital transport times were long. Concordance between codes in the registry and the reference standard was moderate, influencing individual patients’ injury code validity, but not aggregated group injury severity score. The majority were examined with CT, predominately SWBCT. DLP for a SWBCT was slightly above national reference levels. There was no difference in injury severity and frequency of interventions between children and adults. The high proportion of patients with minor injuries and the significantly lower use of CT among children, indicate that use of a selective CT examination strategy in a higher proportion of the patients would have approximated the ICRP’s justification ...